MiR-155-5p：在肾母细胞瘤中表达下调并抑制肾母细胞瘤细胞的增殖、迁移及促进细胞凋亡 (Nan Fang Yi Ke Da Xue Xue Bao, 2019)
OBJECTIVE: explore the expression of miR-155-5p in Wilms tumor and its effect in regulating the proliferation, migration and apoptosis of Wilms tumor cells. METHODS: Specimens of tumor tissues and paired adjacent tissues were obtained from 40 patients with Wilms tumor for detection of the expression levels of miR-155-5p using RT-qPCR. Wilms tumor cell line G401 was transfected with miR-155-5p mimics and miR-155-5p inhibitor to induce miR-155-5p over-expression and its inhibition, respectively, and the changes in the cell proliferation, migration and apoptosis were assessed using cell counting kit-8 (CCK-8), wound healing assay and fl ow cytometry. RESULTS: RT-qPCR showed that the expression of miR-155-5p decreased significantly in Wilms tumor tissues as compared with normal kidney tissues and was significantly associated with TNM stage (P < 0.05). In G401 cells, over-expression of miR-155-5p significantly inhibited the cell proliferation and migration and promoted cell apoptosis (P < 0.05), and down-regulation of miR-155-5p obviously enhanced the proliferation and migration and suppressed apoptosis of the cells (P < 0.05). CONCLUSION: miR-155-5p is down-regulated in Wilms tumor and its expression level is correlated with TNM stage. miR-155-5p participates in the progression of Wilms tumor by inhibiting the proliferation and migration and promoting apoptosis of the tumor cells, and may serve as a novel biomarker for diagnosis, therapy and prognostic evaluation of Wilms tumor.